Pengembangan Media Boneka Tangan Pada Pembelajaran Tema 3 Benda di Sekitarku Kelas III Sekolah Dasar - Nadiatul Hasanah (PT. ALHAFI BERKAH INDONESIA, 2024)
This research aims o determine the development of hand puppet media on the learning interest of class III at SDN 16 Sungai Pinyuh. The research method used is the (Risearch & Development) mehod, while the research model used is 4-D with the stages of designing, defining, developing and disseminating. The sample included in this research, namely class III students at SDN 16 Sungai Pinyuh, totaled 52 students consisting of 23 male and 29 famale. The validation technique used is a validation questionnaire for material experts and media experts. Data collection uses student response questionnaires and interest assessments. Data analysis techniques are used to determine the feasibility, practicality and effectiveness of hand puppet media. The research results show: 1) feasibility, 2) practicality, and 3) effectiveness. Media expert validation obtained a total score of 100% in the “very worthy” category. Meanwhile, material expert validation obtained a total score of 87,5% in the “very feasible” category. Field trials measure the practicality of the product through 3 stages, namely individual scale field tests, small scale field tests and large scale field tests. With student response quentionnaires the average total score 98.0% in the “very practical” category. Meanwhile, field trials to measure effectiveness only used large-scale field tests and the effectiveness field tests obtained an overall test score of 4,0 in the “very effetive” category. With the media developed by researchers created to help the enthusiasm of students who lack interest in learning so they can achieve the desired learning goals. The conclusion is that hand puppet media is feasible, practical and effective to be used as a learning medium for the theme 3 Objects Around Me in Class III in Elementary School.